A multi-tracer approach to constraining water sources of culturally and ecologically significant natural springs: Combining environmental isotopes and environmental DNA - Monica Esmond; Dioni Cendón; Harald Hofmann; Mark de Bruyn; Matthew Currell (Journal of Hydrology, 2026)

EveryOne, EveryWhere, EveryWhen: Just water futures for three Living Rivers - R. Quentin Grafton; Anne Poelina; William Brian (Badger) Bates; Matthew Currell; David Doyle; Kirsty Howey; Cecilia Lake; Caroline McFarlane; Anthony McLarty; Nhat-Mai Nguyen; Sam Phelan; Patricia Riley; et al. (Water Security, 2026)

Occurrence and transport of per- and polyfluoroalkyl substances (PFAS) within a coastal groundwater aquifer - Oliver A.H. Jones; Alexander Brindle; Mikaela Sterjovski; Shadha Al-Mashari; Pacian Netherway; Phoebe Lewis; Jennifer Martin; Matthew Currell (Journal of Contaminant Hydrology, 2026)

A simplified drought indicator based on high-resolution GRACE terrestrial water storage anomalies - Ikechukwu Kalu; Christopher E. Ndehedehe; Vagner G. Ferreira; Sreekanth Janardhanan; Matthew Currell; Oluwafemi E. Adeyeri; Onuwa Okwuashi; Mark J. Kennard (Journal of Hydrology, 2025)

Using geochemical and geophysical data to characterise inter-aquifer connectivity and impacts on shallow aquifers and groundwater dependent ecosystems - Angus G. Campbell; Ian Cartwright; John A. Webb; Dioni I. Cendón; Matthew J. Currell (Applied Geochemistry, 2025)

Iman Peoples Water Sovereignty: Extractive Industries in Central Queensland - Clint J. Hansen; Matthew J. Currell; Eugenia Flynn (The Extractive Industries and Society, 2024)

Multiple isotope tracers reveal the sources of water sustaining ecologically and culturally significant springs, and their vulnerability to mining development - Angus G. Campbell; Ian Cartwright; Dioni I. Cendón; Matthew J. Currell (Journal of Hydrology, 2024)

Intensive agriculture, a pesticide pathway to >100 m deep groundwater below dryland agriculture, Cordoba Pampas, Argentina - Agustín Cabrera; Dioni I. Cendón; Virginia Aparicio; Matthew J. Currell (Journal of Hydrology, 2024)

Using major ions and stable isotopes to improve conceptualisation of a spring-aquifer system in the Galilee Basin, Australia - Robin Keegan-Treloar; Eddie W. Banks; Ian Cartwright; Dylan J. Irvine; John A. Webb; Adrian D. Werner; Matthew J. Currell (Hydrogeology Journal, 2024)
Developing conceptual models is a critical step in hydrogeological studies that should utilise multiple lines of evidence and data types to minimise conceptual uncertainty, particularly in data-sparse systems. This study used new and existing major ion and isotope (O, H, Sr, C) data sets to refine a previous hydraulic-head-based conceptual model of the Galilee Basin (Australia). The analyses provide evidence for the locations of recharge and discharge areas and determine hydrochemical processes along flow paths to improve understanding of potential source waters to the Doongmabulla Springs Complex (DSC) and to infer mixing within, or exchange between aquifer units. There was good agreement between previously inferred recharge and discharge areas defined using hydraulic head data and interpretations from hydrochemical evolution along groundwater flow pathways, at least where data were available. Major ion and isotope data suggest that the DSC likely receives water from both a relatively shallow, local flow path and a deeper regional flow path. This observation is relevant to previous concerns about threats to the DSC, as mine-induced drawdown may impact the relative contributions to spring discharge from different recharge sources and aquifers. Silicate weathering in the deeper Clematis Formation and Dunda Beds, and evapotranspiration in the overlying Moolayember Formation have strong control on the total dissolved solids content. These findings suggest that the Clematis Formation and Dunda Beds are hydrochemically distinct from the Moolayember Formation, with limited exchange between these aquifers, which has important implications for model conceptualisation and ongoing monitoring of mining activities in the Galilee Basin.

Examining changes in groundwater PFAS contamination from legacy landfills over a three-year period at Australia's largest urban renewal site - Matthew Currell; Nathan Northby; Pacian Netherway (Chemosphere, 2024)

Celebrating a pioneer in geochemical tracer science for groundwater and surface water research: Professor Ian Cartwright - Dylan J. Irvine; Matthew J. Currell; Harald Hofmann (Applied Geochemistry, 2023)

Review of Endocrine Disrupting Compounds (EDCs) in China's water environments: Implications for environmental fate, transport and health risks - Yi Xiao; Dongmei Han; Matthew Currell; Xianfang Song; Yonghong Zhang (Water Research, 2023)

Fellowship of the Spring: An initiative to document and protect the world's oases - Roderick J. Fensham; Rouhollah Adinehvand; Sally Babidge; Marco Cantonati; Matthew Currell; Linda Daniele; Alper Elci; Diana M.P. Galassi; África de la Hera Portillo; Salah Hamad; Dongmei Han; Hussain Ali Jawadi; et al. (Science of The Total Environment, 2023)

Screening of Atrazine Distribution in Groundwater and Modeling of Leaching Potential to the Unconfined Aquifer in the Pampean Plain of Cordoba, Argentina - Verónica F. Lutri; Mónica T. Blarasin; Edel M. Matteoda; Matthew Currell; Daniela B. Giacobone; Fátima Bécher Quinodóz; Adriana E. Cabrera (Environmental Processes, 2022)

Environmental isotopes as indicators of groundwater recharge, residence times and salinity in a coastal urban redevelopment precinct in Australia - Emily Hepburn; Dioni I. Cendón; Dawit Bekele; Matthew Currell (Hydrogeology Journal, 2020)

A framework and simple decision support tool for groundwater contamination assessment in an urban redevelopment precinct - Emily Hepburn; Anne Northway; Dawit Bekele; Matthew Currell (Hydrogeology Journal, 2019)

Cultivating hope for a better future: research contributions from young scholars in earth and environmental sciences - Peiyue Li; Ken W. F. Howard; Matthew Currell (Environmental Science and Pollution Research, 2017)

Geochemical indicators of the origins and evolution of methane in groundwater: Gippsland Basin, Australia - Matthew Currell; Dominic Banfield; Ian Cartwright; Dioni I. Cendón (Environmental Science and Pollution Research, 2017)

Editors’ Message: The 2014 Editors’ Choice articles and the 2014 ‘Coolest Paper’ award - Clifford Voss; Matthew Currell (Hydrogeology Journal, 2015)

Stable isotopes as indicators of water and salinity sources in a southeast Australian coastal wetland: identifying relict marine water, and implications for future change - Matthew J Currell; Peter Dahlhaus; Hiroyuki Ii (Hydrogeology Journal, 2015)

Mega-scale groundwater quality challenges and the need for an inter-disciplinary approach - Matthew Currell (Hydrogeology Journal, 2014)

Editors’ Message: The 2013 Editors’ Choice articles, a new editor, and the 2013 ‘Coolest Paper’ award - Clifford Voss; Matthew Currell; Tom Gleeson (Hydrogeology Journal, 2014)

Erratum: Analysis of environmental isotopes in groundwater to understand the response of a vulnerable coastal aquifer to pumping: Western Port Basin, south-eastern Australia - Matthew Currell; Dioni I. Cendón; Xiang Cheng (Hydrogeology Journal, 2013)

Analysis of environmental isotopes in groundwater to understand the response of a vulnerable coastal aquifer to pumping: Western Port Basin, south-eastern Australia - Matthew Currell; Dioni I. Cendón; Xiang Cheng (Hydrogeology Journal, 2013)

Major-ion chemistry, δ13C and 87Sr/86Sr as indicators of hydrochemical evolution and sources of salinity in groundwater in the Yuncheng Basin, China - Matthew J. Currell; Ian Cartwright (Hydrogeology Journal, 2011)

Hydrogeochemical Indicators of Groundwater Flow Systems in the Yangwu River Alluvial Fan, Xinzhou Basin, Shanxi, China - Dongmei Han; Xing Liang; Menggui Jin; Matthew J. Currell; Ying Han; Xianfang Song (Environmental Management, 2009)